Advanced endoscopic ultrasound management techniques for preneoplastic pancreatic cystic lesions - DUMAN, DENİZ (BMJ PUBLISHING GROUP, 2017)
Pancreatic cystic lesions can be benign, premalignant or malignant. The recent increase in detection and tremendous clinical variability of pancreatic cysts has presented a significant therapeutic challenge to physicians. Mucinous cystic neoplasms are of particular interest given their known malignant potential. This review article provides a brief but comprehensive review of premalignant pancreatic cystic lesions with advanced endoscopic ultrasound (EUS) management approaches. A comprehensive literature search was performed using PubMed, Cochrane, OVID and EMBASE databases. Preneoplastic pancreatic cystic lesions include mucinous cystadenoma and intraductal papillary mucinous neoplasm. The 2012 International Sendai Guidelines guide physicians in their management of pancreatic cystic lesions. Some of the advanced EUS management techniques include ethanol ablation, chemotherapeutic (paclitaxel) ablation, radiofrequency ablation and cryotherapy. In future, EUS-guided injections of drug-eluting beads and neodymium:yttrium aluminum agent laser ablation is predicted to be an integral part of EUS-guided management techniques. In summary, International Sendai Consensus Guidelines should be used to make a decision regarding management of pancreatic cystic lesions. Advanced EUS techniques are proving extremely beneficial in management, especially in those patients who are at high surgical risk.
Keywords: Pancreatic Neoplasms; Endoscopy; Pancreatic Carcinoma; Pancreatic Diseases; GUIDED RADIOFREQUENCY ABLATION; PAPILLARY MUCINOUS NEOPLASMS; DIFFERENTIAL-DIAGNOSIS; SINGLE INSTITUTION; ETHANOL-LAVAGE; ULTRASONOGRAPHY; CANCER; TUMORS; TRIAL; SCLEROTHERAPY